(untitled) (Práxis Educativa, 2022)
This work presents a bibliographical analysis of 15 children’s books by Monteiro Lobato from an anti-racist perspective. As a reference for the arguments, studies on race relations, sexism and whiteness developed by several black intellectuals, including Lélia Gonzalez, Grada Kilomba, Nilma Lino Gomes and Conceição Evaristo, permeate the text aiming to transgress the most traditional forms of scientific reflection. However, the theoretical rigor is outlined along these lines in which urgent questions evade the silences and expose themselves. It is concluded that instigating new conceptions and confronting a racist country is part of an education committed to dismantling injustice and indifference towards black and indigenous populations. Keywords: Monteiro Lobato. Racism. Children’s Literature.